Pengembangan Modul Flipbook Digital dengan Pendekatan STEM untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMP - Dhini Maulidiyah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Critical thinking skills are one of the skills needed to deal with learning in the 21st century. Critical thinking skills will involve activities, such as interpreting, analyzing, evaluating, concluding, explaining the results of one's thinking, and how to make decisions and apply new knowledge. Students' critical thinking skills in Indonesia are still relatively low. The low critical thinking skills of students are due to the fact that many teachers still use learning media that is less varied. Modules in the form of digital flipbooks are defined as learning media to simplify material and independent learning with electronic media can be an alternative to improve critical thinking skills. This research aims to produce a valid, practical, and effective Science, Technology, Engineering, and Mathematics (STEM)-based digital flipbook module. This development research (R&D) uses the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate). Data collection was done through various techniques, including observation, interviews, questionnaires, tests, and documentation. The instruments used to collect data include validation sheets, learning implementation observation sheets, test sheets, and student response questionnaires. The result of product validity is 92% which is criticized as very valid. The result of learning practicality is 97.89% criticized as practical. The result of the effectiveness of the average pre-test and post-test scores with the N-gain test is 0.65 criticized as moderate. The result of the student response questionnaire score is 96.81% which is very good. Based on these results, it is concluded that the digital flipbook module developed is said to be feasible to use to improve the critical thinking skills of junior high school students.
Repository Januari 2026_Hasyim
Keywords: Critical thinking; Digital Flipbook; ADDIE model; STEM